2019
DOI: 10.1111/fwb.13255
|View full text |Cite
|
Sign up to set email alerts
|

Competition during early ontogeny: Effects of native and invasive planktivores on the growth, survival, and habitat use of bluegill

Abstract: Early life stages of fishes are sensitive to ecological and environmental disturbances and experience very high mortality rates. During early ontogeny, the growth and survival of larval fish often depends on food availability. Because habitat and diet shifts are strongly tied to individual body size, factors that influence the growth rates of individuals (e.g. resource limitation, competition) also affect other aspects of ontogeny including the timing of habitat or diet shifts. In the context of biological inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…A number of studies have demonstrated that competition can have negative impacts on fish growth, survival or fitness (e.g. Werner & Gilliam, 1984;Persson, 1983aPersson, , 1987Byström et al, 1998;Britton et al, 2018;Fletcher et al, 2019). In spite of the differences in foraging ecology observed in this study, there were no significant differences in the growth or condition of roach or bream larvae in allopatry and sympatry (cf., Britton et al, 2018), suggesting that the strength of competition and/or the duration of the experiment were insufficient to have a measurable effect.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…A number of studies have demonstrated that competition can have negative impacts on fish growth, survival or fitness (e.g. Werner & Gilliam, 1984;Persson, 1983aPersson, , 1987Byström et al, 1998;Britton et al, 2018;Fletcher et al, 2019). In spite of the differences in foraging ecology observed in this study, there were no significant differences in the growth or condition of roach or bream larvae in allopatry and sympatry (cf., Britton et al, 2018), suggesting that the strength of competition and/or the duration of the experiment were insufficient to have a measurable effect.…”
Section: Discussionmentioning
confidence: 49%
“…Other possible explanations include that the fish density was too low, but this also seems unlikely as it was more than an order-of-magnitude higher than in some successful experiments of density-dependent growth (e.g. Byström et al, 1998;Byström & García-Berthou, 1999;Fletcher et al, 2019). However, although absolute density was constant, and comparable with those observed in the wild (e.g.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Widespread invasion of silver carp has had substantial ecological and economic effects on freshwater ecosystems in the United States (Fletcher et al ., 2019; Freedman et al ., 2012; Solomon et al ., 2016; Zhang et al ., 2015). Larval silver carp compete with juvenile sport fishes for resources, creating an upstream effect on their population and ultimately the economy that is supported by such fisheries (Fletcher et al ., 2019; Solomon et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Widespread invasion of silver carp has had substantial ecological and economic effects on freshwater ecosystems in the United States (Fletcher et al ., 2019; Freedman et al ., 2012; Solomon et al ., 2016; Zhang et al ., 2015). Larval silver carp compete with juvenile sport fishes for resources, creating an upstream effect on their population and ultimately the economy that is supported by such fisheries (Fletcher et al ., 2019; Solomon et al ., 2016). Later in ontogeny, silver carp can consume particles as small as 5 μm, but also regularly consume those as large as 100 μm and compete with fish species across the entire trophic hierarchy (Battonyai et al ., 2015; Cremer & Smitherman, 1980; Smith, 1989; Zhou et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%